PENINGKATAN KARIR GURU DI SMK SWASTA BM TELADAN MEDAN - Ambarita, Charles Fransiscus (JGK (Jurnal Guru Kita), 2019)
Abstract: Teacher Career Improvement in BM Exemplary Private Vocational School Medan. Survey Sites at BM Teladan Jl. Pukat IV No. 52, Bantan Timur Village, Medan Tembung Subdistrict, Medan, North Sumatra. The time of the survey was conducted in February 2018. All subjects in the BM Exemplary Vocational School were the subjects in this study. The technique of collecting data through interviews and direct observation to the Exemplary BM Vocational School with speakers, namely the Principal. In the field observation process, there are still many teachers who have not been certified even though they have become senior teachers, there are still many teachers who have not been able to apply various types of learning models, and many teachers who have not been able to use learning media. This problem causes the teacher to hamper in developing his career. Based on the results of research at the BM Exemplary Private Vocational School, Medan, data obtained that the number of teachers who have carried out professionalization in the development of teacher careers is still relatively low. Of the 22 teachers there were only 11 teachers who had made certification. Keywords: Teacher’s Career, Teacher Professionalism, Teacher Certification Abstrak: Peningkatan Karir Guru di SMK Swasta BM Teladan Medan. Tempat Survey di SMK BM Teladan Jl. Pukat IV No. 52, Kelurahan Bantan Timur, Kecamatan Medan Tembung, Medan, Sumatera Utara. Waktu survey dilakukan pada Februari 2018. Yang menjadi subjek dalam penelitian ini adalah semua guru di SMK BM Teladan. Teknik pengambilan data melalui wawancara dan observasi langsung ke SMK BM Teladan dengan narasumber yaitu Kepala Sekolah.Pada proses observasi dilapangan ditemukan masih banyak guru yang belum sertifikasi meskipun sudah menjadi guru senior, masih banyaknya guru yang belum mampu menerapkan berbagai macam model pembelajaran, dan masih banyak guru yang belum dapat menggunakan media pembelajaran. Permasalahan inilah yang menyebabkan terhambatnya guru dalam mengembangkan karirnya. Berdasarkan hasil penelitian di SMK SWASTA BM Teladan Medan, diperoleh data bahwa jumlah guru yang telah melaksanakan profesionalisasi dalam perkembangan karir guru masih tergolong rendah. Dari 22 guru hanya terdapat 11 guru yang telah melakukan sertifikasi. Kata Kunci : Karir Guru, Profesionalitas Guru, Sertifikasi Guru